Self‐Healable and 4D Printable Hydrogel for Stretchable Electronics - Huijun Li; Chin Boon Chng; Han Zheng; Mao See Wu; Paulo Jorge Da Silva Bartolo; H. Jerry Qi; Yu Jun Tan; Kun Zhou (Advanced Science, 2024)
Abstract Materials with high stretchability and conductivity are used to fabricate stretchable electronics. Self‐healing capability and four‐dimensional (4D) printability are becoming increasingly important for these materials to facilitate their recovery from damage and endow them with stimuli–response properties. However, it remains challenging to design a single material that combines these four strengths. Here, a dually crosslinked hydrogel is developed by combining a covalently crosslinked acrylic acid (AAC) network and Fe3+ ions through dynamic and reversible ionically crosslinked coordination. The remarkable electrical sensitivity (a gauge factor of 3.93 under a strain of 1500%), superior stretchability (a fracture strain up to 1700%), self‐healing ability (a healing efficiency of 88% and 97% for the mechanical and electrical properties, respectively), and 4D printability of the hydrogel are demonstrated by constructing a strain sensor, a two‐dimensional touch panel, and shape‐morphing structures with water‐responsive behavior. The hydrogel demonstrates vast potential for applications in stretchable electronics.